2003
DOI: 10.1242/jcs.00635
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle behavior of human HP1 subtypes: distinct molecular domains of HP1 are required for their centromeric localization during interphase and metaphase

Abstract: Heterochromatin protein 1 (HP1) plays an important role in heterochromatin formation. Three subtypes of HP1, namely HP1α, β, and γ, have been identified in humans. In this study, using yellow fluorescent protein(YFP) fusion constructs, we examined the intracellular localization of human HP1 subtypes during the cell cycle. During interphase, all three HP1 subtypes were localized to centromeric heterochromatin and to promyelocytic leukemia(PML) nuclear bodies. Different preferences, however, were observed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 54 publications
16
126
0
3
Order By: Relevance
“…Moreover, ubiquitously expressed HP1 isoforms show differential chromosomal distributions, as HP1a is mainly associated to heterochromatin, while HP1c is excluded from centromeric heterochromatin and HP1b is found both at euchromatic and heterochromatic domains (Smothers and Henikoff 2001). A similar situation is observed in mammals, where the patterns of localiza-tion of the three HP1 isoforms (HP1␣, HP1␤, and HP1␥) overlap only partially and show differential dynamics during differentiation and cell cycle progression (Minc et al 1999;Hayakawa et al 2003;Dialynas et al 2007). On the other hand, in the nematode Caenorhabditis elegans, two HP1 isoforms exist (HPL1 and HPL2), showing preferential euchromatic association, partially nonoverlapping expression and localization patterns, and distinct mutant phenotypes Schott et al 2006).…”
mentioning
confidence: 66%
“…Moreover, ubiquitously expressed HP1 isoforms show differential chromosomal distributions, as HP1a is mainly associated to heterochromatin, while HP1c is excluded from centromeric heterochromatin and HP1b is found both at euchromatic and heterochromatic domains (Smothers and Henikoff 2001). A similar situation is observed in mammals, where the patterns of localiza-tion of the three HP1 isoforms (HP1␣, HP1␤, and HP1␥) overlap only partially and show differential dynamics during differentiation and cell cycle progression (Minc et al 1999;Hayakawa et al 2003;Dialynas et al 2007). On the other hand, in the nematode Caenorhabditis elegans, two HP1 isoforms exist (HPL1 and HPL2), showing preferential euchromatic association, partially nonoverlapping expression and localization patterns, and distinct mutant phenotypes Schott et al 2006).…”
mentioning
confidence: 66%
“…Also intriguing is the dissociation between chromatin condensation and HP1␤ accumulation observed during the early phases of chromatin remodeling caused by nuclear transfer (Martin et al, 2006). Unlike metaphase chromosomes (Minc et al, 1999), HP1␤-abundant chromocenters are restored in somatic cells and in mESCs at G1 phase (Hayakawa et al, 2003;Martin et al, 2006). This is not observed during the G1 phase after nuclear transfer into the oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies using different cell lines and experimental approaches have shown partial to complete loss of HP1 from mitotic chromatin. [43][44][45][46][47][48] The consensus seems that at this stage of the cell cycle, all of HP1b and HP1g, as well as the majority of HP1a, dissociate from chromatin. Only a fraction of HP1a remains localized at the centromeres.…”
Section: Mitotic Release Of Hp1 From Chromatinmentioning
confidence: 99%